Validating Dimensions of Mobile Service Quality e-Commerce Consumer to Consumer (C2C) in Indonesia from Seller's Perspective - Pradana, Bayu Ilham; Parwati, Kardina Yudha; Ardian, Faril; Li, Nancy Runnan (Jurnal Aplikasi Manajemen, 2024)
Along with technological advancement, many sellers in Indonesia have shifted to use digital platform like e-commerce, which is creating potential ecosystem for various e-commerce applications to grow and face intense competition in facilitating direct transactions between consumers (C2C). This study aims to confirm the mobile service quality dimensions of e-commerce on mobile applications. The study adopts a quantitative approach with sellers who are use of popular C2C mobile applications in Indonesia, such as Tokopedia, Shopee, Bukalapak, and TikTok Shop as the population. Sample selection using purposive technique resulted in a sample size of 313 respondents. Testing was conducted using Confirmatory Factor Analysis (CFA) to determine the proposed dimensions of e-commerce mobile application service quality from previous research. The results of the study confirm six factors of mobile service quality in e-commerce applications: Application Design, Reliability, Responsiveness, Trust, Efficiency, and System Availability. Testing with the modified model provides higher fit criteria. ANOVA was used to compare components in each dimension. E-commerce service providers can use the reÂsult to improve service quality. These improvements involve refining the apÂplication interface, ensuring reliability, responsiveness, security, efficiency, and system availability, aiming to boost user satisfaction, foster continued app usage, and fortify the service provider's reputation.